Adaptation of Luborsky’s Core Conflictual Relationship Theme (CCRT) method : a phenomenological case study - Schoeman, J.B. (University of Pretoria, 2013)
Dissertation (MA (Clinical Psychology))--University of Pretoria, 2007.